Neurodynamic, Cognitive, and Personal Characteristics of Foreign Students during Adaptation to University Environment - Lidia A. Varich; Elena S. Zhelonkina; Irina S. Morozova (Вестник Кемеровского государственного университета. Серия: гуманитарные и общественные науки)
Foreign students have to adapt to new linguacultural academic environment. The adaptation process affects their neurodynamic, cognitive, and personal indicators. The research involved such psychophysiological parameters as nervous system lability, visual-motor reactions, memory scope, and attention span. The paper introduces the personality profile of an average foreign student, as well as substantiates the importance of neurodynamic, cognitive, and personal indicators during adaptation. In this research, foreign students demonstrated situational rather than personal anxiety, compared with their Russian peers. They developed fatigue associated with poor functional state of the central nervous system. The adaptation peculiarities depended on the nationality: this fact has to be taken into account to optimize adaptation to the new academic environment. The neurodynamic and cognitive features correlated with Russian proficiency. Those that did not speak Russian had poor visual-motor reaction, nervous system lability, memory scope, and attention span, which correlated with maladaptation to the new linguacultural academic environment.